Multifunctional derivatives of dimethoxy-substituted triphenylamine containing different acceptor moieties - Gudeika, Dalius; Bundulis, Arturs; Benhattab, Safia; Ben Manaa, Marwa; Berton, Nicolas; Bouclé, Johann; Tran Van, François; Schmalt, Bruno; Volyniuk, Dmytro; Rutkis, Martins; Grazulevicius, Juozas V. (Springer Nature Switzerland AG, 2020)
Two compounds, having dimethoxy-substituted triphenylamino groups and fragments of cyanoacrylic acid or rhodanine-3-acetic acid were prepared and characterized. Their optical, photophysical, thermal, electrochemical, photoelectrical and nonlinear optical properties were investigated. Both derivatives showed ability of glass-formation with glass transition temperatures of 83 and 61 °C. They showed comparable ionization potential values of ca. 5.20 eV. The compounds showed Kerr and two photon absorption effects. The dye containing a rhodanine-3-acetic acid fragment, namely 2-((E)-5-(4-(diphenylamino)benzylidene)-tetrahydro-4-oxo-2-thioxothiophen-3-yl)acetic acid, exhibited a promising power conversion efficiency of 2.09% in dye-sensitized solar cells using the spiro-OMeTAD as hole transporting compound.
This project has received funding from the Research Council of Lithuania (LMTLT), Agreement No. [S-LZ-19-2]. This research was funded by the Région Centre, the Tunisian ministry of research, University of Monastir and the French ministry of Higher Education and Research. J. Bouclé would like to thank the Sigma-Lim LabEx environment for financial supports, and the PLATINOM facility at XLIM laboratory regarding device fabrication and characterizations. DG acknowledges the Lithuanian Academy of Sciences for the financial support.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Dimethoxy-substituted triphenylamine; Cyanoacrylic acid; Rhodanine-3-acetic acid; Dye-sensitized solar cell; Two photon absorption effect; Kerr effect